Points of Improvement: Reflective Strategy to Support Chilean EFL Pre-Service Teachers' Lesson Planning - Nataly Telles Quezada; María-Jesús Inostroza Araos; Maritza Rosas-Maldonado (Asociación Colombiana de Profesores de Ingles, 2019)
This action research study aims to explore the contribution of the use of points of improvement as a reflective strategy to support eleven Chilean EFL pre-service teachers' ability to plan communicative-oriented lessons. Through questionnaires and a focus group, participants' responses were examined using thematic analysis. Findings yielded that their beliefs about communicative-oriented lessons were in fact linked with the communicative approach. Lastly, their perceptions towards the use of points of improvement as a reflective strategy showed more awareness in the classroom, narrowing the gap between their pedagogical and disciplinary knowledge.